A brief 20‐item dental/medical health literacy screen (REALMD‐20). (7th January 2013) - Gironda, Melanie; Der‐Martirosian, Claudia; Messadi, Diana; Holtzman, Jennifer; Atchison, Kathryn
Abstract Objectives Few health literacy instruments are available to clinicians to help understand the implications of patient difficulty understanding health information. Those that do exist are lengthy and would not be conducive to use in a busy clinical setting. Long‐term dental and medical outcomes may improve if health care providers can identify individuals with low health literacy levels who may benefit from tailored communication, yet few instruments are available for clinical use. The purpose of this study is to introduce a brief 20‐item screener for limited dental/medical health literacy among adult dental patients. Methods Two‐hundred adult patients seeking treatment at a dental clinic in a large medical complex completed a health literacy screening instrument and survey. Steps in the development of the 20‐item instrument are described. Comparison of the 20‐item dental/medical instrument with other health literacy measures are calculated using mean health literacy scores, tests of reliability and readability, and correlation coefficients. Results Scores on the brief 20‐item measure varied significantly by race, education level, language use, needing help with medical/health materials forms. Those with lower dental/medical health literacy, as measured by the REALMD‐20 were less likely to receive regular follow‐up care than those with higher literacy. Conclusions The REALMD‐20 is a quick screening instrument that can be used by clinicians to detect limited dental/medical health literacy among adult patients seeking treatment in dental/medical clinic settings.